Removal of fluoxetine from water by adsorbent materials produced from paper mill sludge - Jaria, Guilaine
In this work, three adsorbents were produced by using as precursor primary paper mill sludge and applying KOH, NaOH or ZnCl2 as chemical activating agents (PS800-10KOH, PS800-10NaOH and PS800-10ZnCl2) and subjected to pyrolysis. The produced materials were tested for removal of fluoxetine from water, reported as one of the most persistent pharmaceuticals in the aquatic environment. Also, primary sludge pyrolysed under the same conditions but without activation (PS800-10) and a commercial activated carbon (PBFG4) were studied for comparison. Physical and chemical properties of the materials were determined and adsorption kinetic and equilibrium studies were performed in batch experiments. Equilibrium studies allowed testing the capacity of the produced materials for adsorb fluoxetine-HCl, showing no apparent correlation between the SBET areas and the adsorption capacities of the materials. The maximum adsorption capacity (mg g 1) was of 191.6 ± 4.8 for PS800-10KOH; 136.6 ± 9.6 for PS800-10NaOH; 28.4 ± 0.3 for PS800-10ZnCl2; 120.4 ± 2.5 for PS800-10 and 96.2 ± 1.0 for PBFG4. It was demonstrated that many factors influence the removal of fluoxetine from solution and that the surface area is not the main factor in the process. Also the activation process did not enhance the properties of the produced materials.